Strategi Komunikasi Organisasi Untuk Meningkatkan Motivasi Kerja Karyawan Di RSUD Lahat: Strategi Komunikasi Organisasi Untuk Meningkatkan Motivasi Kerja Karyawan Di RSUD Lahat - Windi Wulandari; Hamidah; Muhammad Randicha Hamandia (CV. ITTC INDONESIA, 2023)
Organizational Communication is a form of exchanging messages between communication units within an organization. Organizations consist of communication units in a hierarchical relationship with one another and function within an environment. In addition, in the exchange of information from employees and leaders, the expectations of employees and the will of the leadership merge into one to form a common perception, vision and mission of the company. The company is an organization consisting of a group or system of individuals who generally strive to achieve predetermined goals through a hierarchy of rank and division of labor as well as in an organization, both on a small and large scale, where all problems meet, namely communication. Where communication cannot be one-way within a company, namely from superiors to subordinates, but also must be two-way and reciprocal so that what all parties want can be realized properly. This research was conducted with the consideration of seeing that the Lahat Hospital turned out to be the strategy implemented was still not able to increase employee motivation. It can be seen that there are still employees who are not responsible for their work, namely going in and out during working hours. This can affect work productivity, this situation arises because the strategy is not optimal.